Biodegradation of polyethylene by microalgae Anabaena sp. and Chlorococcum sp. - Palanisamy, Karthick Murugan; Maniam, Gaanty Pragas; Mohd Hasbi, Ab. Rahim; Govindan, Natanamurugaraj (AIP Publishing, 2024)
These accumulations of used plastics like high-density polyethylene (HDPE) and low-density polyethylene (LDPE) cause environmental pollution in various way. Biological treating method can be an alternative of solution for reducing the accumulation of plastics in our environment. In this study, Plastic samples were pre-treated by placing under exposure of ultraviolet (320±10 nm) for 5 days continuously. Then, placed in the microalgae Anabaena sp. culture and Chlorococcum sp. culture for biological treatment for 21 days. FTIR and SEM been used and observed the functional group changes and surface changes on polyethylene. From the biological treatment between treated polyethylene and microalgae found that both microalgae shown well grown. In LDPE found greater growth of Chlorococcum sp. higher than Anabaena sp. HDPE does not shown any obvious changes in growth of microalgae. FTIR result shown the changes in mechanical structure of LDPE by reduction of ester groups -(C-C-O-C-C)- after biological treated with Chlorococcum sp. Visual changes as pattern of round rupture circle found on the surface of LDPE as compared HDPE which analyzed though FESEM result.